Philosophy of physics a very short introduction - Wallace, David 1976- (Oxford, United Kingdom Oxford University Press, 2021)
Philosophy of Physics: A Very Short Introduction explores the core topics of philosophy of physics through three key themes: the nature of space and time; the origin of irreversibility and probability in the physics of large systems; how we can make sense of quantum mechanics. Central issues discussed include: the scientific method as it applies in modern physics; the distinction between absolute and relative motion; the way that distinction changes between Newton's physics and special relativity; what spacetime is and how it relates to the laws of physics; how fundamental physics can make no distinction between past and future and yet a clear distinction exists in the world we see around us; why it is so difficult to understand quantum mechanics, and why doing so might push us to change our fundamental physics, to rethink the nature of science, or even to accept the existence of parallel universes. -- Provided by publisher.
The methods and fruits of science -- Motion and inertia -- Relativity and its philosophy -- Reduction and irreversibility -- Mysteries of the quantum -- Interpreting the quantum.
Includes bibliographical references (pages 133-138) and index.
Keywords: Quantum theory; Physics -- Philosophy